TNFR2 is critical for TNF-induced rheumatoid arthritis fibroblast-like synoviocyte inflammation. (8th March 2022) - Suto, Takahito; Tosevska, Anela; Dalwigk, Karolina; Kugler, Maximillian; Dellinger, Mirjam; Stanic, Irena; Platzer, Alexander; Niederreiter, Birgit; Sevelda, Florian; Bonelli, Michael; Pap, Thomas; Kiener, Hans; et al.
Abstract: Objectives: TNF-induced activation of fibroblast-like synoviocytes (FLS) is a critical determinant for synovial inflammation and joint destruction in RA. The detrimental role of TNF-receptor 1 (TNFR1) has thoroughly been characterized. The contributions of TNFR2, however, are largely unknown. This study was performed to delineate the role of TNFR2 in human FLS activation. Methods: TNFR2 expression in synovial tissue samples was determined by immunohistochemistry. Expression of TNFR2 was silenced using RNAi or CRISPR/Cas9 technologies. Global transcriptional changes were determined by RNA-seq. QPCR, ELISA and immunoblotting were used to validate RNA-seq results and to uncover pathways operating downstream of TNFR2 in FLS. Results: TNFR2 expression was increased in RA when compared with OA synovial tissues. In particular, RA-FLS demonstrated higher levels of TNFR2 when compared with OA-FLS. TNFR2 expression in RA-FLS correlated with RA disease activity, synovial T- and B-cell infiltration. TNF and IL1β were identified as inflammatory mediators that upregulate TNFR2 in RA-FLS. Silencing of TNFR2 in RA-FLS markedly diminished the TNF-induced expression of inflammatory cytokines and chemokines, including CXCR3-binding chemokines and the B-cell activating factor TNFSF13B. Immunobiochemical analyses revealed that TNFR2-mediated expression of inflammatory mediators critically depends on STAT1. Conclusion: Our results define a critical role for TNFR2 in FLS-driven inflammation and unfold its participation in the unresolved course of synovial inflammation in RA.